Evaluation of arsenic contamination and potential health risk through water intake in urban and rural areas. Issue 6 (7th June 2021) - Rasool, Atta; Muhammad, Said; Shafeeque, Muhammad; Ahmad, Iftikhar; Al-Misned, Fahad A.; El-Serehy, Hamed A.; Ali, Salar; Murtaza, Behzad; Sarwar, Abid
Abstract: Arsenic (As) is a global public health and environmental problem because of its non-degradable and toxic nature. This study was carried out to assess the As contamination and potential health risk through water intake in rural and urban areas. Water samples were collected from urban and rural areas of Kahror Pacca, Punjab, Pakistan, and then, analyzed for As concentration. The concentrations of As in water samples were 1.62 − 35.28 and 3.23 − 45.62 μg/L for the rural and urban areas, respectively. The spatial distribution of As-rich shallow groundwater specifies their direct contamination through anthropogenic influence and agricultural practices. The chronic risk exposure was evaluated based on the determined As through hazard quotient, average daily dose, and cancer risk. Results disclosed that hazard quotient values were > 1 in studied drinking water samples. The cancer risk due to As consumption surpassed the threshold limits defined by the United States environmental protection agency (1.0E-04 to 1.0E06). Statistical analyses, including principal component analyses and Pearson correlation, suggested that As contamination in drinking water was imputed to both geogenic and anthropogenic reasons. It is revealed that intake of As contaminated water might result in various cancer problems to the community in the future. Research Highlights: Arsenic concentration surpassed WHO drinking water guidelines Arsenic has hazard quotient values > 1 through electric pump water consumption Statistical analysis revealed geogenic and anthropogenic activities contributed to water contamination